Trauma team discord and the role of briefing. Issue 1 (July 2016) - Steinemann, Susan; Bhatt, Ajay; Suares, Gregory; Wei, Alexander; Ho, Nina; Kurosawa, Gene; Lim, Eunjung; Berg, Benjamin
Abstract : BACKGROUND: Briefing of the trauma team before patient arrival is unstructured in many centers. We surveyed trauma teams regarding agreement on patient care priorities and evaluated the impact of a structured, physician-led briefing on concordance during simulated resuscitations. METHODS: Trauma nurses at our Level II center were surveyed, and they participated in four resuscitation scenarios, randomized to "briefed" or "nonbriefed." For nonbriefed scenarios, nurses independently reviewed triage sheets with written information. Briefed scenarios had a structured 4-minute physician-led briefing reviewing triage sheets identical to nonbriefed scenarios. Teams included three to four nurses (subjects) and two to four confederates (physicians, respiratory therapists). Each team served as their own control group. Confederates were blinded to nurses' briefed or nonbriefed status. Immediately before, and at the midpoint of each scenario, nurses estimated patients' morbidity and mortality and ranked the top 3 of 16 designated immediate care priorities. Briefed and nonbriefed groups' responses were compared for (1) agreement using intraclass correlation coefficient, (2) concordance with physicians' responses using the Fisher exact test, (3) teamwork via T-NOTECHS ratings by nurses and physicians using t -test, and (4) time to complete clinical tasks using t test. RESULTS: Thirty-eight nurses participated. Ninety-seven percent "agreed/strongly agreed" briefing is important, but only 46% agreed briefing was done well. Comparing briefed versus nonbriefed scenarios, nurses' estimation of morbidity and mortality in the briefed scenarios showed significantly greater agreement with each other and with physicians' answers ( p < 0.01). Rank lists also better agreed with each other (intraclass correlation coefficient, 0.64 vs 0.59) and with physicians' answers in the briefed scenarios. T-NOTECHS Leadership ratings were significantly higher in the briefed scenarios (3.70 vs 3.39; p < 0.01). Time to completion of key clinical tasks was significantly faster for one of the briefed scenarios. CONCLUSIONS: Discordant perceptions of patient care goals was frequently observed. Structured physician-led briefing seemed to improve interprofessional team concordance, leadership, and task completion in simulated trauma resuscitations.